Engineering PQS biosynthesis pathway for enhancement of bioelectricity production in pseudomonas aeruginosa microbial fuel cells - Wang, Victor Bochuan (2013)
The biosynthesis of the redox shuttle, phenazines, in Pseudomonas aeruginosa, an ubiquitous microorganism in wastewater microflora, is regulated by the 2-heptyl-3,4-dihydroxyquinoline (PQS) quorum-sensing system. However, PQS inhibits anaerobic growth of P. aeruginosa. We constructed a P. aeruginosa strain that produces higher concentrations of phenazines under anaerobic conditions by over-expressing the PqsE effector in a PQS negative ΔpqsC mutant. The engineered strain exhibited an improved electrical performance in microbial fuel cells (MFCs) and potentiostat-controlled electrochemical cells with an approximate five-fold increase of maximum current density relative to the parent strain. Electrochemical analysis showed that the current increase correlates with an over-synthesis of phenazines. These results therefore demonstrate that targeting microbial cell-to-cell communication by genetic engineering is a suitable technique to improve power output of bioelectrochemical systems.